Analisis Kompetensi Tenaga Tata Usaha Untuk Meningkatkan Kualitas Administrasi Sekolah Di SD Satit Phatnawitya Thailand - Nurhakiki; Ramlah, Siti (STIT Sirojul Falah Bogor, 2023)
This study aims to describe the competence of administrative staff in improving the quality of education administration at Satit Phatnawitya Elementary School in Thailand. The type of this research is descriptive qualitative which describes and examines the real conditions of the object of research based on authentic data collected. The research subjects consisted of the principal, 2 administrative staff, 5 teachers and 3 students. Data collection techniques using observation, interviews and documentation. The results of this study indicate that: the competence of administrative staff at SD Satit Phatnawitya Thailand in carrying out their duties can be carried out properly. Be it personal competence, social competence, and managerial competence. However, it still needs to be improved regarding technical competence, especially with regard to the efficiency of working time, this is because the quantity of administrative staff is still lacking. In addition, they also double as an educator (teacher) this is what causes the quality of performance to not be carried out optimally. As for the efforts made to improve the quality of education administration, they try to do excellent service by doing work outside working hours (overtime) to complete tasks. In addition, they also prioritise and establish good cooperation by filling each other's shortcomings between colleagues (administrative staff).